2017
DOI: 10.12973/ejmste/80764
|View full text |Cite
|
Sign up to set email alerts
|

Higher Education Development Path Based on Practical Education Pattern

Abstract: Since the ancient times, there have been the cultural tradition of valuing knowledge more than its practical usage. With the development of social economy and the requirement of modernization construction, the talent quality required by enterprises is becoming higher and higher, which makes the structural contradiction of higher education become more and more prominent. The training mechanism which is adopted by colleges and universities for training applied, compound and innovative talents cannot meet the nee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
(24 reference statements)
0
4
0
Order By: Relevance
“…Based on several experts' opinions about evaluation (Adnan et al, 2019;Andrade, 2019;Chen, 2017;Gu, 2020;JH & Baderiah, 2020;Ratminingsih et al, 2018;Wirawan et al, 2018;Yahiji et al, 2019;Yudianto et al, 2019), it can be concluded that evaluation is an activity planned to assess the achievement of a program for decision making. In addition, it is stated by Republic of Indonesia Law Number 20/2003 article 57 paragraph (1) on the National Education System that evaluation is carried out in order to control the quality of education nationally as a form of teachers' and institutions' accountability to interested parties.…”
Section: Discussionmentioning
confidence: 99%
“…Based on several experts' opinions about evaluation (Adnan et al, 2019;Andrade, 2019;Chen, 2017;Gu, 2020;JH & Baderiah, 2020;Ratminingsih et al, 2018;Wirawan et al, 2018;Yahiji et al, 2019;Yudianto et al, 2019), it can be concluded that evaluation is an activity planned to assess the achievement of a program for decision making. In addition, it is stated by Republic of Indonesia Law Number 20/2003 article 57 paragraph (1) on the National Education System that evaluation is carried out in order to control the quality of education nationally as a form of teachers' and institutions' accountability to interested parties.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, other challenges are facing higher education institutions, such as inadequate teaching and learning opportunities and resources, insufficient funding of the academic program, weak links between industry and education, lack of competent teachers, etc. which also affects learning outcomes (Chen, 2017).…”
Section: Review Of Literature Researches and Reports Of State And International Organizationsmentioning
confidence: 99%
“…The principal goal of the lecturer is to motivate students to study the course material, to demonstrate the relevance and practical importance of that material and to enhance students’ research curiosity (Brown et al, 2015; Chen, 2017; Dicheva et al, 2018; Friesen et al, 2018; Landers, 2014).…”
Section: Machine-building Hydraulics In a Technical University Curricmentioning
confidence: 99%